Testing the taxonomy of Dmanisi hominin fossils through dental crown area - Victor Nery; Walter Neves; Leticia Valota; Mark Hubbe (PLoS ONE, 2025)
The Dmanisi paleoanthropological assemblage from Georgia is among the most debated collections of hominin fossils due to its early age and extreme morphological diversity relative to other Homo assemblages. This variability has been interpreted as a result of sexual dimorphism in the Homo erectus clade, in which Dmanisi hominins were traditionally classified. However, this hypothesis has been challenged by the proposal that the Dmanisi fossils represent more than one Homo species. Taxonomic assessments of the Pleistocene Georgian hominins have focused primarily on craniometric analyses, with fewer studies addressing dental morphology through metric approaches. Considering the value of dental crown area in reconstructing evolutionary relationships, a comparative sample of fossil hominins, consisting of 51 maxillary and 71 mandibular specimens (583 teeth in total), was analyzed using Linear Discriminant Analysis (LDA) to evaluate the diversity in the Dmanisi fossil assemblage. Morphological affinities were examined visually through the first two discriminant functions, and taxonomic relationships were tested via classification analyses based on posterior probabilities. The analyses show a strong association of the D4500-D2600 specimen with australopiths, and of the D2282-D211 and D2700-D2735 specimens with Homo species. The sexual dimorphism hypothesis was tested by comparing the ratios of mandibular postcanine dentition of Dmanisi specimens with male and female gorillas and chimpanzees, which suggests that dental crown area of the Pleistocene Georgian hominins could be the product of sexual dimorphism only if they came from species with similar levels of dimorphism than these great apes. We conclude that differences in crown dimensions support the hypothesis of two distinct taxa coexistent at the Dmanisi site, previously proposed to be Homo georgicus and Homo caucasi . This proposal has important implications for the dispersal of Homo out of Africa at the beginning of Pleistocene.